Effects of different hand paddle sizes on bilateral propulsive force difference in the front crawl swimming - Carvalho Barbosa, A.; Andries Junior, O. (Serbian Journal of Sports Sciences, 2011)
This study investigated the effect of different sizes of hand paddles on bilateral propulsive force difference (BFD) in the crawl stroke. Fourteen male swimmers (Age: 20.0 ± 3.7 years, 100-m best time: 53.70 ± 0.87 s) were submitted to the following test protocol: 2 x 10 s maximal efforts in the fully tethered swimming, repeated in five conditions: free swimming (FREE), with small (PP, 280 cm²), medium (PM, 352 cm²), large (PG, 462 cm²) and extra-large paddles (PGG, 552 cm²). Stronger (STR) and weaker (WKR) strokes were those which presented the higher and lower mean peak force values in four non-consecutive strokes, respectively. BFD was expressed by the percentage difference between STR and WKR. STR and WKR were significantly different in all the situations (FREE: 30.2 x 25.4 kgf; PP: 31.6 x 26.9 kgf; PM: 33.0 x 29.0 kgf; PG: 34.5 x 30.3 kgf; PGG: 36.0 x 31.6 kgf). No specific paddle size changed BFD significantly. A significant reduction occurred when the lower individual values of BFD obtained with hand paddles, independently of their size, were compared to those found in FREE (14.9% x 7.4%). The present results showed that the artificial enlargement of hands can acutely reduce the bilateral force difference in competitive swimmers. However, the best size of paddles should be individually chosen.